Prenatal exposure to tap water containing nitrate and the risk of small-for-gestational-age: A nationwide register-based study of Danish births, 1991–2015. (April 2023) - Jensen, Anja Søndergaard; Coffman, Vanessa R.; Schullehner, Jörg; Trabjerg, Betina B.; Pedersen, Carsten B.; Hansen, Birgitte; Olsen, Jørn; Pedersen, Marie; Stayner, Leslie T.; Sigsgaard, Torben
Abstract: Background: Prenatal nitrate exposure from household tap water has been associated with increased risk of fetal growth restriction, preterm birth, birth defects, and childhood cancer. We aim to examine the association between maternal consumption of drinking-water nitrate during pregnancy and small-for-gestational-age (SGA) in a nationwide study of Danish-born children, as only one prior study has examined this association. Methods: We linked individual-level household estimates of nitrate in tap water and birth registry data to all live singleton Danish births during 1991–2015 from Danish-born parents where the mother resided in Denmark throughout the pregnancy. Exposure was both binned into four categories and modeled as an ln-transformed continuous variable. SGA was defined as the bottom 10% of births by birth weight per sex and gestational week. Multiple logistic regression models with generalized estimating equations were used to account for siblings born to the same mother while controlling for relevant confounders. Results: In the cohort of 1, 078, 892 births, the median pregnancy nitrate exposure was 1.9 mg/L nitrate. Compared to the reference group (≤2 mg/L), we found an increased risk of SGA in the second category (>2–5 mg/L) (OR = 1.04, 95% CI: 1.03–1.06) and third category (>5–25 mg/L) (OR = 1.02, 95% CI: 1.00–1.04) but not in the highest (>25 mg/L). There was strong (p = 0.002) evidence of an increase in SGA with nitrate in the model with continuous exposure (OR = 1.02, 95% CI: 1.01–1.04 per 10-fold increase in nitrate). Results were robust when restricting to households with nitrate levels at or below the current Danish and European Union regulatory drinking water standard (50 mg/L nitrate). Conclusions: Our findings suggest that exposure from nitrate in household tap water, even below current regulatory standards, may increase risk of SGA, raising concerns of whether current allowable nitrate levels in drinking water protect children from SGA.